2018
DOI: 10.1111/exd.13674
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of the skin barrier structures revealed by electron microscopy

Abstract: The barrier function of skin is indispensable for terrestrial animals. This function is mainly carried out by the epidermis, more specifically by its granular and cornified layers. The major structural components associated with this function are the intercellular lipid layer, desmosomes, corneodesmosomes, tight junctions, cornified cell envelope and keratin filaments. In this review, we discuss the current knowledge of their ultrastructure, their molecular basis and their relevance to skin disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 55 publications
1
21
0
1
Order By: Relevance
“…Cldn: claudin, JAM: junctional adhesion molecule, Ocln: Occludin, ZO: zonola occludens protein. ( E ) Composition and structure of the basement membrane, ( A ) modified from [ 19 ], ( B ) from [ 20 ], ( C ) from [ 21 ], ( D ) from [ 2 ], ( E ) from [ 22 ].…”
Section: Which Skin Barriers Have To Be Overcome?mentioning
confidence: 99%
“…Cldn: claudin, JAM: junctional adhesion molecule, Ocln: Occludin, ZO: zonola occludens protein. ( E ) Composition and structure of the basement membrane, ( A ) modified from [ 19 ], ( B ) from [ 20 ], ( C ) from [ 21 ], ( D ) from [ 2 ], ( E ) from [ 22 ].…”
Section: Which Skin Barriers Have To Be Overcome?mentioning
confidence: 99%
“…It has been previously shown that after TGN exit, LBs carry the Rab11a GTPase known for its regulatory role in vesicular trafficking (Ishida-Yamamoto et al, 2018;Reynier et al, 2016). Among Rab11a effectors, one of the most frequently reported is the actin-based molecular motor, Myo5b.…”
Section: Actin-based Myo5b Is Associated With Lb Markers In Granular mentioning
confidence: 99%
“…The physical barrier of the epidermis is formed by proteinenriched corneocytes with their cornified envelopes (CEs) and by lipid-enriched intercellular domains (Akiyama, 2017;Ishida-Yamamoto et al, 2018). A previous report demonstrated the physical fragility of CE isolated from DMKN-bg -/mouse skin .…”
Section: Dmkn-abg -/Mouse Skin Exhibits Fragile Cornified Envelopesmentioning
confidence: 99%